Optimising Employee Performance through Placement, Work Environment, and Achievement Assessment: A Case Study on the Cell Store Mojokerto - Agustina, Ratna; Rachmawati, Eny (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Human resource management cannot be separated from the employee factor which is expected to be able to perform as best as possible to achieve organizational goals. To achieve organizational goals effectively, of course, quality human resources (workforce) are needed in their fields. This research aims to find out and analyze how to optimize performance by focusing on the suitability of work placement, work environment, and work performance assessment both simultaneously and partially. The type of research used in this study is quantitative research. The population and sample in this study include all employees of Toko Cell Mojokerto totaling 45 people. The data analysis methods used in this study are instrument tests, classical assumption tests, multiple linear regression analysis tests, t-test and F tests, and determination coefficient tests. The results of this study show that there is a partial and simultaneous influence between the variables of suitability of work placement, work environment, and achievement assessment on employee performance at the Mojokerto Cell Store